Diseño de una estrategia educativa de enfermería para la atención de mujeres y sus familias frente al duelo perinatal. (2023)
Perinatal grief is defined as the process of physiological adaptation of parents and the family environment to the loss of their baby, either during pregnancy or during the first days of the baby's life. This phenomenon of acceptance after the death of a child generates a series of physical, emotional and psychological consequences in those who suffer it. In addition, some complications may occur, such as the development of pathological grief or psychiatric disorders